Placental Apoptosis in Small for Gestational Age Babies: A Comparison between Swedish and Pakistani Populations - Akram, Shahzad; Simatou, Eleni; Stukenborg, Jan-Bernd; Hagenäs, Lars; Söder, Olle; Bhutta, Zulfiqar A. (International Journal of Child Health and Nutrition, 2014)
Background: Foeto-placental growth is regulated by a complex balance of growth promoting and growth inhibiting factors and hormones, namely the insulin-like growth factors (IGF) and the intracellular caspase proteins. Changes in the IGF-axis appear to affect this balance, with deficiencies possibly triggering apoptosis. Aim: To ascertain levels of apoptosis in the placenta of infants born small for gestational age (SGA) and appropriate for gestational age (AGA), comparing samples from two population groups, Pakistani and Swedish, in an attempt to better understand the mechanism behind foetal-placental growth restriction. Methods: Placental samples were taken immediately following delivery in both Karachi and Stockholm. In total 36 samples were included for further analysis (Pakistani: SGA n = 12, AGA n = 12; Swedish: SGA n = 7, AGA n = 5). Protein extraction was conducted for cell-death ELISA, and the remaining tissue samples were then paraffin embedded for further immunohistochemical and immunoflourescent analysis, looking at the apoptotic proteins, p53, caspase 8, and caspase 3. Furthermore, we compared maternal and newborn anthropometry between populations. Results: A higher apoptotic index, for caspase 8 and caspase 3, was seen in the Pakistani samples, as compared to the Swedish samples (p<0.01). TUNEL assays showed higher levels of apoptosis in the Pakistani population as compared to the Swedish population (p<0.01). Cell death ELISA analysis showed greater apoptotic activity in placenta from the Pakistani population as compared to the Swedish groups (p<0.05) as well as increased apoptotic activity in the SGA groups as compared to the AGA groups within each population (ELISA, p<0.05). No differences were seen in p53 levels as assessed by immunohistochemistry. Pakistani mothers were, on average, shorter than their Swedish counterparts (p<0.01). Conclusion: Increased apoptotic activity in placenta of the Pakistani population, as compared to their Swedish counterparts, may be associated with decreased foetal-placental growth seen in this population, particularly in babies born SGA. These findings, along with previously published results of the IGF-axis, and birth weight outcomes, suggests that lower IGF levels may be involved in the extracellular triggering of apoptosis, through caspase 8. This may further suggest a possible mechanism of foetal-placental growth restriction.